The use of stacked T-plating in dogs - von Pfeil, D. J. F.; Roush, J. K. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Dogs with fractures of the distal femur (one case), ilium (two cases) and a corrective osteotomy of the distal tibia (one case) underwent internal fixation using two 3.5-mm T-plates, applied in stacked fashion. Due to the specific configuration of the fractures as well as the size of the dogs, stacked T-plating was considered the most reliable technique to achieve satisfactory repair. All of the cases had “excellent” to “good” outcomes. The clinical experience with these four cases supports the utility of stacked T-plating in fractures with one very short end fragment. Stacked T-plating seems to have distinct advantages over a single 3.5-mm dynamic compression plate. However, due to the small number of cases presented in this report, there is a need for further clinical evaluation and biomechanical studies.
Keywords: Stacked T-plating; short fragmented fractures; dog